Comprehensive evaluation of the aggressive certain degree of the chemical components in water to concrete - Doan, Thy Truc (Frontiers in Built Environment, 2024)
Comprehensive Evaluation of the aggressive certain degree of the chemical components in water to concrete +Comment contents from the Reviewer 4:1. The conclusion of the article is too long. The authors should present it in more concise sentences.2. It will be beneficial if the author can clarify some potential assumptions or these future studies' direction according to their findings.3. The conclusion seems to reaffirm the experiment results, rather than explaining or discussing their significance.4. In the abstract, the results of the study are redundant. It would be helpful for authors to simplify details.